Novel Wideband MIMO Antennas That Can Cover the Whole LTE Spectrum in Handsets and Portable Computers - Mohamed Sanad; Noha Hassan (The Scientific World Journal)
A dual resonant antenna configuration is developed for multistandard multifunction mobile handsets and portable computers. Only two wideband resonant antennas can cover most of the LTE spectrums in portable communication equipment. The bandwidth that can be covered by each antenna exceeds 70% without using any matching or tuning circuits, with efficiencies that reach 80%. Thus, a dual configuration of them is capable of covering up to 39 LTE (4G) bands besides the existing 2G and 3G bands. 2×2 MIMO configurations have been also developed for the two wideband antennas with a maximum isolation and a minimum correlation coefficient between the primary and the diversity antennas.